Estimation of drug users and injecting drug users in Malaysia - Mohamed, Mahmood Nazar (Universiti Utara Malaysia Press, 2005)
Malaysia treats the problem of drug addiction as a security issue.Since it was identified in the early 70’s, the number of drug addicts is constantly on the rise.At present, the government provides all statistics pertaining to the number of drug users, abusers and addicts in the country.The monograph contains the full report that was submitted to the Ministry of Health and WHO-WPR. It reports the national data for drug addiction for the year 2002, and a detailed description of the methodology used to arrive at the estimates.